2017
DOI: 10.1371/journal.pone.0171475
|View full text |Cite
|
Sign up to set email alerts
|

Tangshen formula attenuates diabetic renal injuries by upregulating autophagy via inhibition of PLZF expression

Abstract: The Chinese herbal granule Tangshen Formula (TSF) has been proven to decrease proteinuria and improve estimated glomerular filtration rate (eGFR) in diabetic kidney disease (DKD) patients. However, the underlying mechanism of TSF on treatment of diabetic nephropathy (DN) remains unclear. The present study aimed to identify the therapeutic target of TSF in diabetic renal injuries through microarray-based gene expression profiling and establish its underlying mechanism. TSF treatment significantly attenuated dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…The cells were divided into the following groups: the OA group and the PA group, which were grown with 50 μM oleic acid and 50 μM sodium palmitate, respectively. The PA+TSF 250 and PA+TSF 500 groups were treated with 50 μM sodium palmitate + 250 μg/mL TSF and 50 μM sodium palmitate + 500 μg/mL TSF, respectively (Zhao et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were divided into the following groups: the OA group and the PA group, which were grown with 50 μM oleic acid and 50 μM sodium palmitate, respectively. The PA+TSF 250 and PA+TSF 500 groups were treated with 50 μM sodium palmitate + 250 μg/mL TSF and 50 μM sodium palmitate + 500 μg/mL TSF, respectively (Zhao et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The degree of glomerulosclerosis was calculated by the percentage of extracellular matrix (ECM) deposition and mesangial expansion and evaluated at 400X power in 20 cortical fields. The mesangial matrix was scored as follows: 1, <10%; 2, 10–25%; 3, 26–50%; 4, 51–75%; 5, 76–95%; 6, >95% (Zhao et al, 2017 ). The renal sections (8 μm) of fixed frozen mouse kidneys were prepared for Oil Red O and filipin cholesterol staining.…”
Section: Methodsmentioning
confidence: 99%
“…A recent prospective, multicenter, double-blind, randomized, controlled study has demonstrated the significant benefit of TSF in decreasing proteinuria and improving estimated glomerular filtration rate in DKD patients compared with placebo [ 12 ]. Further studies indicate TSF may attenuate DKD by inhibiting zinc finger and BTB domain containing 16 (ZBTB16/PLZF) expression [ 13 ], transforming growth factor beta (TGF-β)/SMAD family member 3 (Smad3)/nuclear factor kappa B subunit (NF-κB) signaling pathways [ 14 ], and activating Janus kinase (JAK)/signal transducer and activator of transcription (STAT)/suppressor of cytokine signaling (SOCS) signaling pathway [ 15 ]. However, the mechanism of TSF in DKD treatment remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this study was to further explore the molecular mechanisms of TSF treatment for DKD by collecting microarray dataset GSE90842 from the National Center of Biotechnology Information Gene Expression Omnibus (NCBI GEO) public database [ 13 ] and analyzing it by a series of bioinformatics software. Compared with the study of Zhao et al [ 13 ], a non-strict threshold (P<0.05 and |logFC (fold change) | >0.1 vs. |logFC| >0.5) was selected to obtain more differentially-expressed genes (DEGs), and DEGs were run between the 2 groups by t test but not among the 3 groups by one-way ANOVA. The crucial DEGs were subsequently identified by construction of a protein and protein interaction (PPI) network and module analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation